Accountability as a Sub-Type of Justice: Reflections on 'Obedience' and 'Religion' in Aquinas's Summa Theologiae. (August 2021) - Case, Brendan
This article proposes that we recognize 'accountability' as a forward-looking virtue, which disposes its possessors to live accountably in relation to those to whom they are rightly answerable, and which can be sub-divided into 'particular accountability', exercised within specific and limited relationships, and 'ultimate accountability', regarding the shape of one's life as a whole. The article then proposes that these two forms of accountability find close analogues in two virtues which Thomas Aquinas described as 'annexed to justice', namely 'obedience' (accountability to human superiors) and 'religion' (accountability to God).